A study on premium packaging for fresh agricultural products - Nik Wan, Noh; Abd Ghani, Siti Mariam; Mohamed, Mohd Fadzli; Said, Rusmawati; Abdul Halim Lim, Sarina; Kamarulzaman, Nitty Hirawaty (Federal Agricultural Marketing Authority, 2023)
This paper provides a value proposition and an assessment of customer value based on producers and consumer-perceived quality to utilize premium packaging for agricultural products. This paper concentrates on assessing the definition of premium packaging from customers perspectives, trends in fruits and vegetables premium packaging and studying the marketing implications resulting from the use of premium packaging. A total of 386 consumers and 54 wholesalers completed the questionnaire. The data were analyzed using descriptive analysis, comparison of mean test and finally SWOT analysis was implemented to suggest strategic actions. Most of the respondents are interested in purchasing agricultural products using premium packaging. The most common products identified for premium packaging are red apples, tomato, celery, and flowers. The impact of household income is identified by the willingness to pay premium packaging for agricultural products according to household income. Because a premium image is of critical importance for many consumer goods, it is important for both designers and marketers to have a comprehensive understanding of the packaging characteristics that can evoke such a premium perception. The present research integrates knowledge from design research and marketing research to enhance the understanding of the role of packaging design in shaping consumers product perceptions. Considerations when designing premium packaging could be four premium cues (extraordinary differentiation, high quality of packaging materials, minimalistic design, and authenticity) as important guidelines. When these premium cues are implemented in a packaging design, consumers will recognize the product as a superior, high-quality product that is worth a higher price.